2013
DOI: 10.4172/1948-5956.1000197
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Chemotherapy using the Anti-Diabetic Drug, Metformin, as an “Adjuvant”: An Exploratory Study

Abstract: Cancer remains one of the most challenging diseases to treat in this new millennium. In an attempt to increase tumor response rates and decrease patient toxicity to various chemotherapeutic agents, the efficacy of metformin as a chemosensitizer was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In correlation with our pilot studies we also observed that even though DCA was able to induce mitochondrial depolarization (Figure 2), we observed highly variable induction of apoptosis or necrosis when DCA was used as a single agent, or even as a chemosensitizer (Figure 1). Nonetheless, long and continuous in vivo exposure may be required as demonstrated by Bradford and Khan [33] and/or DCA may cause cell growth inhibition without causing apoptosis [34] and hence account for minimal in vitro results noted in the third decade (apoptosis) and thus account for the clinical 'stable disease' case noted above(as well as other unpublished cases observed at Medicor Cancer Centres)…”
Section: Resultsmentioning
confidence: 99%
“…In correlation with our pilot studies we also observed that even though DCA was able to induce mitochondrial depolarization (Figure 2), we observed highly variable induction of apoptosis or necrosis when DCA was used as a single agent, or even as a chemosensitizer (Figure 1). Nonetheless, long and continuous in vivo exposure may be required as demonstrated by Bradford and Khan [33] and/or DCA may cause cell growth inhibition without causing apoptosis [34] and hence account for minimal in vitro results noted in the third decade (apoptosis) and thus account for the clinical 'stable disease' case noted above(as well as other unpublished cases observed at Medicor Cancer Centres)…”
Section: Resultsmentioning
confidence: 99%
“…Such low risk in both sexes may be associated with metformin usage. Many observational studies reported decreased cancer incidence and cancer-related mortality in type 2 diabetics receiving standard doses of metformin therapy (35,36,37,38,43,44,45) .…”
Section: Resultsmentioning
confidence: 99%
“…Do randomized controlled clinical trials have to be planned to further correlate and validate these tests and to fully appreciate their impact on cancer recurrence and survival rates? [29] "Yes" BUT this is difficult, especially in light of the fact that cancer is practically the only malady that is heterogenic, and hence how do you design and compare, for example, one person's carcinoma of the breast (testis, cervix, endometrium prostate, etc, etc) with another person's carcinoma of the breast (testis, cervix, endometrium prostate, etc, etc) when they are ALL likely to respond differently to different agents? Our lab has obtained 'anecdotal' information due to the failure of a "group z" patients to standard regimens, and thus we used non-protocol agents [i.e.…”
Section: Postscriptmentioning
confidence: 99%
“…Our lab has obtained 'anecdotal' information due to the failure of a "group z" patients to standard regimens, and thus we used non-protocol agents [i.e. metformin, DCA] [29,30] that were successful. Is this anecdotal information useless?…”
Section: Postscriptmentioning
confidence: 99%